About Some Problems of the Methodology of the Study of State and Legal Phenomena - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2021)
This article is devoted to the problems of the methodology of the study of state and legal problems concerning its